(untitled) (Environment & Health, 2017)
Objective: We performed a hygienic assessment of factual nutrition of schoolchildren and determined its impact on mental efficiency in middle-age and senior school age children. Materials and methods: Features of nutrition were studied by means of the questioning of 462 schoolchildren in 5th – 11th grades in the city of Kyiv. Mental efficiency was investigated with the help of corrective tests with a further statistic processing of all obtained data. Results: Factual nutrition of modern schoolchildren is characterized by the insufficient consumption of such foodstuffs as meat, butter, eggs, dairy produce in 22 % of the children, fish and sea products – in 60 % of the children. In general the malnutrition is typical for 19 % of middle-age schoolchildren and 16 % of senior age ones. Results of integral assessment showed that a number of children with malnutrition increased and decreased with optimum nutrition from 5th to 9th grades (p < 0,001). A connection of the increase of the productivity of mental efficiency with a growth of integral assessment of nutrition was established (rs = 0.12; p < 0.001). Isolated contribution of “nutrition” factor in the productivity of mental efficiency is 7.3 ± 0.4 % (p